The Optimization Management of Combination Research Methods in Improving the Quality of Writing Research Reports - Nasruddin, Nasruddin; Umiyati, Hesti; Fadil, Kevin Refano (APTISI Transactions on Management (ATM), 2019)
Management in writing research reports is a crucial activity for a researcher who wants to publish his research results. The research method is a method used to get results and discussion of research. In this study, the research method was used to explain the characteristics of quantitative, combination and qualitative methods with as many as 12 (twelve) points, and literature studies on the definition of 4 (four). The core of this study discusses management of the philosophical foundation of combination research, the characteristics of quantitative, qualitative and combination methods. Then discussed also the definition of combination methods, the nature of the combination method, variations of combination methods, combination research methods models: combination model or sequential explanatory design, combination model or sequential exploratory design, combination model or concurrent triangulation design and model combination method or concurrent embedded design. By doing this research, it is hoped that it can add insight to the authors of research reports regarding the management of combination research methods.